Dissecting the mechanism of signaling-triggered nuclear export of newly synthesized influenza virus ribonucleoprotein complexes - Schreiber, André (Proc Natl Acad Sci U S A, 2020)
Influenza viruses (IV) exploit a variety of signaling pathways. Previous studies showed that the rapidly accelerated fibrosarcoma/mitogen-activated protein kinase/extracellular signal-regulated kinase (Raf/MEK/ERK) pathway is functionally linked to nuclear export of viral ribonucleoprotein (vRNP) complexes, suggesting that vRNP export is a signaling-induced event. However, the underlying mechanism remained completely enigmatic. Here we have dissected the unknown molecular steps of signaling-driven vRNP export. We identified kinases RSK1/2 as downstream targets of virus-activated ERK signaling. While RSK2 displays an antiviral role, we demonstrate a virus-supportive function of RSK1, migrating to the nucleus to phosphorylate nucleoprotein (NP), the major constituent of vRNPs. This drives association with viral matrix protein 1 (M1) at the chromatin, important for vRNP export. Inhibition or knockdown of MEK, ERK or RSK1 caused impaired vRNP export and reduced progeny virus titers. This work not only expedites the development of anti-influenza strategies, but in addition demonstrates converse actions of different RSK isoforms.